Japanese Education in a Global Age Sociological Reflections and Future Directions (Education in the Asia-Pacific Region: Issues, Concerns and Prospects, 2018)
This book highlights recent education research on Japan based on sociological and other related approaches to historical developments and accomplishments. Written primarily by members of the Japan Society of Educational Sociology, it brings to light concerns and viewpoints that have grown out of the Japanese educational context. By focusing on uniquely Japanese educational research phenomena, the book offers international readers new insights and contributes to the international debate on education. It may help sociologists and social scientists outside Japan gain a deeper understanding of ongoing changes in education in Japan as well as its historical and structural contexts.